Regulatory changes, reporting quality and audit fees: the moderating role of firm characteristics - Abdulmalik O, Salau (2016)
The objective of this study is to investigate the effect of regulatory changes on financial reporting quality and audit fees and to further test whether this effect was moderated by firm characteristics (i.e. abnormal audit fees, political connections and overlapping directorship) in Nigeria. This study utilised the data of 90 companies listed on the Nigerian stock exchange over the periods 2008-2013. Using Generalized Method of Moments (GMM) technique that takes into account the endogeneity nature of financial reporting quality and audit fees model, the results indicated that financial reporting quality improved in the regulatory changes period. However, abnormal audit fees, political connection and overlapping directorship deteriorated the effect. In addition, the study found an increase in the amount paid as audit fees in the regulatory changes periods and this varied with the perceived riskiness of firm characteristics. Specifically, the increase in financial reporting quality in the regulatory changes periods led to a decrease in audit fees while the perceive riskiness of overlapping directorship increased audit fees in the regulatory changes periods. Further, the perceived riskiness of politically connected firms in the regulatory changes periods did not significantly affect audit fees. Accordingly, future regulatory reforms must be cognizant of these factors. Even though there are abundant empirical studies on financial regulatory changes and their effects on financial reporting quality and audit fees, this study provides additional insights into the regulatory change literature by investigating how firms characteristics (abnormal audit fees, political connection and overlapping directorship) moderates the effect of regulatory changes particularly in Nigeria, one of the less developed and under researched capital markets in the world. Further, the findings of this study are robust with respect to the issues of unobserved heterogeneity and endogeneity which previous studies had failed to consider.